Modulation of the gut-bone axis: Lacticaseibacillus paracasei LC86 improves bone health via anti-inflammatory metabolic pathways in zebrafish models of osteoporosis and cartilage damage - Dong, Yao; Sun, Yukun; Zhou, Zhipeng; Gai, Zhonghui; Cai, Yihui; Han, Mei; Zou, Kang (Frontiers in Immunology, 2025)
AimOsteoporosis and cartilage injury are major health concerns with limited treatment options. This study investigates the therapeutic effects of Lacticaseibacillus paracasei LC86 (LC86) on osteoporosis and cartilage damage in a zebrafish (Danio rerio) model, focusing on its modulation of the gut-bone axis and its potential mechanisms for enhancing bone health.MethodsA Dexamethasone-induced zebrafish model was used to mimic osteoporosis and cartilage injury. Zebrafish were divided into control, model, and LC86 treatment groups (3×107 CFU/mL). Bone and cartilage health were assessed using Alizarin red staining and fluorescence microscopy. Bone marker expression (sp7, runx2a, bmp2a, bmp4, and col2a1a) was quantified via qPCR. Metabolic alterations were analyzed using untargeted metabolomics, and changes in gut microbiota were examined through 16S rRNA gene sequencing.ResultsLC86 treatment significantly improved bone and cartilage health, as evidenced by increased fluorescence intensity in the skull, hard bone, and cartilage (p < 0.01, p < 0.05). qPCR results showed upregulation of key bone-related genes (sp7, runx2a, bmp2a, bmp4, and col2a1a), indicating enhanced bone and cartilage structure. Metabolomics analysis revealed alterations in over 300 metabolites, with changes in anti-inflammatory and energy pathways. Gut microbiota analysis demonstrated an increase in beneficial bacteria and a decrease in pathogenic genera.ConclusionsLC86 significantly improved bone health, cartilage structure, and gut microbiota composition in a Dexamethasone-induced zebrafish model, supporting its potential as a therapeutic strategy for osteoporosis and cartilage injury via modulation of the gut-bone axis.